Mathematical modeling and optimization of wear-resistant material selection for technological tooling of internal combustion engines - Drach, I.; Valchuk, I. (Problems of Tribology, 2026)
The study develops an integrated approach for selecting wear-resistant materials for technological devices used in machining and repair of internal combustion engines, considering mechanical, thermal, economic, and reliability factors. KHVG and R6M5 steels were comparatively analyzed using modified abrasive wear models, Weibull reliability assessment, and Life Cycle Cost (LCC) analysis. The model accounts for temperature-induced hardness degradation, lubrication conditions, contact geometry, and coating adhesion. It was established that at temperatures above 400 °C and severe abrasive wear, R6M5 steel provides longer service life and reduces LCC by 6–19% compared to KHVG steel. Under moderate temperatures and impact loading, KHVG steel is preferable due to higher fracture toughness. Optimal heat treatment regimes were determined for both steels. Lubrication increases service life by approximately 66%, while risk mitigation measures are more effective than material substitution under high failure probability conditions. TiN coating is not recommended for rough surfaces because of delamination risk. The developed model enables improved engineering decision-making for wear-resistant tooling applications.